PENGGUNAAN BERBAGAI PUPUK KANDANG TERHADAP PERTUMBUHAN SUKUN (Artocarpus Communis Forst) PADA DAERAH TANGKAPAN AIR DANAU TOBA KECAMATAN HARANGGAOL HORISON - Jonny L Hutabarat; Budi Utomo; Afifuddin Dalimunthe (Program studi Kehutanan USU, 2016)
Forest area at catchment area Lake Toba reduced to thousands of acres, resulting in a lot of open land, the land’s ability to absorb water is reduced and became dry land so that land productivity declined catchment area Lake Toba. Breadfruit plants can increase the productivity of land and can be used as plant reforestation to prevent erosion. Manure is manure originating from livestock manure that can memperpaiki structure and texture of the soil, raising the soil absorption of the water, raising the activity of soil microorganisms and as a source of nutrients for plants. The purpose of this study was to determine the effect of various types of manure on the growth of breadfruit.Manure is used is chicken manure, duck manure, goat manure and cow manure. This study was conducted in September-November 2014, at the catcment area Lake Toba, District Haranggaol, Simalungun. Parameters measured were high seed, seed diameter, leaf area, crown area, number of leaves and leaf water content. The results showed that administration of various types of manure significant effect on the growth of breadfruit seeds and the best treatment is chicken manure.Keywords: manure, breadfruit, growth, catchment area